Biomechanical report for the IAAF World Championships London 2017 100 m hurdles Women's - Pollitt, L.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
Billed as one of the most highly anticipated races of the championships, Sally Pearson emerged victorious with a technically flawless display of hurdling, holding off Dawn Harper-Nelson of the USA to win the gold in a time of 12.59 s. Germany`s Pamela Dutkiewicz held off the challenge of the Americans Kendra Harrison and Christine Manning to secure the bronze in 12.72 s; her first global championships medal. Although Pearson did not improve upon her impressive semi-final performance (12.53 s), interestingly the performances of Harper-Nelson and Dutkiewicz were almost identical to their semi-final winning times. The race outcome may have been very different had world record holder (12.20 s) and world lead (12.28 s) Harrison produced the same technical prowess of Pearson. Harrison matched Pearson to the first hurdle and held a slight lead by the third hurdle. However, the cumulative effect of hitting the first hurdle and knocking over the following three meant she lost momentum. By hurdle seven she had slipped down the field and was tied for sixth place. This technical issue almost cost her a place in the final itself. In the semifinal she hit the first hurdle hard and as a result was seventh by hurdle four. Despite hitting all but four hurdles, she managed to fight back and take the last non-automatic qualification place by one hundredth of a second. Her compatriot Manning was also in contention for the gold medal, however, her medal prospects faded after the seventh hurdle. (Attention! registration on the IAAF site is required for downloading)